PERHITUNGAN DINDING PENAHAN TANAH PENANGANAN LONGSORAN RUAS JALAN MARANGKAYU KABUPATEN KUTAI KARTANEGARA - syah, herman (KURVA S JURNAL MAHASISWA, 2014)
Marang Kayu Subdistrict is one of the districts in the coastal region of KutaiKartanegara regency which has reserves of natural resources such as coal,petroleum and natural gas. Marang Kayu Subdistrict rich in natural resourcesinfrastructure is still lagging behind compared to other districts in the coastalarea Regency, including the constraints of land transport infrastructure is stilldamaged in one of its causes avalanches on some streets Marang Kayu. Iflandslides feared would disrupt the flow of traffic so it is necessary the handling ofthe avalanche, one of them is to build a retaining wall construction.In this study retaining wall is planned in two segments, where the segment 1has a length of 20 meters, 3,5 meters high plan, the soles of the foundation 2,5meters wide, 0,50 meters thick soles of the foundation. While in the secondsegment of the planned length of 15 meters high with a plan of 5 meters, the widthof the palm of the foundation 3,5 meters, 0,80 meters thick soles of the foundation.Quality of concrete used is K.300, or 300 kg/cm2.1 segment of calculation obtained 3567,0388 KN largest axial force, so thatthe stability bolsters safe. While the largest shear force 1725,4703 KN andstability against sliding in a safe condition.Obtained from the calculation of segment 2 is 4925,5337 KN largest axialforce, so that the stability bolsters safe. While the largest shear force 2438,73 KNand stability against sliding in a safe condition.